2019
DOI: 10.7748/nop.2019.e1127
|View full text |Cite
|
Sign up to set email alerts
|

Using the Relating to Older People Evaluation tool to measure ageism in higher education

Abstract: The global population is ageing, and this trend is expected to continue. Cultures around the world socialise with older people differently with distinctive attitudes towards ageing. Ageism is a complex multifaceted concept that includes attitudes and behaviours. In the UK, ageism and discriminatory practices exist within nursing, and nurse educationalists and clinicians need to address ageist attitudes and promote older people care as healthcare needs increase. Within the context of nursing there is a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…were significantly associated with the nurses' negative ageism is consistent with previous studies (Burhenn, Shirley Johnson, & Hurria, 2016;Cronin & Brooke, 2019). Burhenn et al (2016) found that knowledge about aging was negatively associated with the nurses' negative ageism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…were significantly associated with the nurses' negative ageism is consistent with previous studies (Burhenn, Shirley Johnson, & Hurria, 2016;Cronin & Brooke, 2019). Burhenn et al (2016) found that knowledge about aging was negatively associated with the nurses' negative ageism.…”
Section: Discussionsupporting
confidence: 91%
“…Burhenn et al (2016) found that knowledge about aging was negatively associated with the nurses' negative ageism. Cronin and Brooke (2019) found that differences in the level of negative ageism among nurses were due to variance in their level of negative attitudes. According to Kang et al (2017), an educational program to improve nurses' knowledge and attitudes toward older adults can decrease nurses' negative ageism and prejudice (Drury, Hutchison, & Abrams, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Herein lies the challenge of determining the optimal delivery of educational interventions designed to prepare students for clinical placements. Recollection following an intervention relies on the time gaps (Groves, Bunch, Cram, & Perkhounkova, 2018) hence, repeating and scaffolding such innovations across curricula are important to maximise recall, reduce the likelihood of continuing ageist attitudes and behaviours developing during the course of the nursing degree (Cronin & Brooke, 2019), and qualify the greater potential of such interventions.…”
Section: Discussionmentioning
confidence: 99%